2014
DOI: 10.5468/ogs.2014.57.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human papillomavirus genotype on severity and prognosis of cervical intraepithelial neoplasia

Abstract: ObjectiveThis study evaluated the effect of the specific human papillomavirus (HPV) genotypes on severity and prognosis in cervical intraepithelial neoplasia (CIN) patients.MethodsThe medical records of 446 patients treated with loop electrosurgical excision procedure (LEEP) were reviewed. The severity of CIN was categorized as CIN1/CIN2 versus CIN3+ including CIN3 and carcinoma in situ (CIS). HPV genotypes were categorized as 1) low risk, 2) intermediate risk, 3) high risk/HPV 16, 4) high risk/HPV 18, and 5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Many risk factors for recurrent dysplasia after conization have been known, but in our study, age, parity, preoperative HPV infection status, major abnormal cytology, treatment modality, margin and gland involvement, and severity of disease were not significant risk factors. Although Ku et al [14] reported that the high-risk HPV 18 genotype is related to resection margin involvement, this was not the case in our study. However, our patients who developed recurrent disease were HPV 16-positive after treatment and had persistent infection.…”
Section: Discussioncontrasting
confidence: 83%
“…Many risk factors for recurrent dysplasia after conization have been known, but in our study, age, parity, preoperative HPV infection status, major abnormal cytology, treatment modality, margin and gland involvement, and severity of disease were not significant risk factors. Although Ku et al [14] reported that the high-risk HPV 18 genotype is related to resection margin involvement, this was not the case in our study. However, our patients who developed recurrent disease were HPV 16-positive after treatment and had persistent infection.…”
Section: Discussioncontrasting
confidence: 83%
“…The benefit of screening for this group of infections is clearly apparent [20] . Ku et al [21] investigated the impact of genotypes on the severity and prognosis of cervical neoplasia, which showed the influence of the virus type on the severity of disease. HPV18 was the most common HPV in their study, but was the second most frequent type in the present study, indicating the divergence of HPV prevalence in differing areas [22] .…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with the present data, which revealed an approximate rate of 50% HR‐HPV positivity. Using HPV typing, Sturegård et al [8] found that the most common (16.7%) high‐risk type was HPV‐16, which is responsible for most intraepithelial neoplasias and carcinomas of the lower genital tract [10,11]. Based on these findings, the authors suggested that vaccination against HPV‐16 and HPV‐18 alone could decrease the incidence of condyloma.…”
Section: Discussionmentioning
confidence: 99%